2017
DOI: 10.1180/minmag.2017.081.012
|View full text |Cite
|
Sign up to set email alerts
|

Trace-element compositions of sapphire and ruby from the eastern Australian gemstone belt

Abstract: Significant uncertainty surrounds the processes involved in the formation of basalt-hosted corundum, particularly the role that the mantle plays in corundum generation. Some previous studies have suggested that trace-element ratios (namely, Cr/Ga and Ga/Mg) are useful for distinguishing two types of corundum: ‘magmatic’ and ‘metamorphic’, designations that include mantle and crustal processes. However, recent studies, including this one, have discovered transitional groups between these end-members that are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 88 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…Twenty-seven spots were measured on both blue and colorless zones (three spots on blue-colored zones of each four sapphire samples, one sapphire sample is completely colorless). Analysis took place in GEOKHI RAS using a New Wave Research UP-213 Nd:YAG laser (New Wave Research, Inc., Fremont, CA, USA) combined with Element-XR (Thermo Finnigan, Waltham, MA, USA) ICP-MS. Trace-element compositions were determined by monitoring 6 Li, 9 Be, 24 Mg, 27 Al, 44 Ca, 47 Ti, 51 V, 53 Cr, 55 Mn, 57 Fe, 59 Co, 60 Ni, 66 Zn, 71 Ga, 88 Sr, 89 Y, 91 Zr, 93 Nb, 181 Ta, 208 Pb, and ablating a material with a spot size of 55 μm at a repetition rate of 4 Hz and an energy density of about 21.17 J/cm 2 . Warm up/background time was 90 s, dwell time was 100 s, and wash out time was 120 s. NIST SRM 610 and NIST SRM 612 glasses (National Institute of Standards and Technology; U.S. Department of Commerce: Gaithersburg, MD) were used as the reference materials and ATHO as an unknown for quality control (QCM).…”
Section: Sapphiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven spots were measured on both blue and colorless zones (three spots on blue-colored zones of each four sapphire samples, one sapphire sample is completely colorless). Analysis took place in GEOKHI RAS using a New Wave Research UP-213 Nd:YAG laser (New Wave Research, Inc., Fremont, CA, USA) combined with Element-XR (Thermo Finnigan, Waltham, MA, USA) ICP-MS. Trace-element compositions were determined by monitoring 6 Li, 9 Be, 24 Mg, 27 Al, 44 Ca, 47 Ti, 51 V, 53 Cr, 55 Mn, 57 Fe, 59 Co, 60 Ni, 66 Zn, 71 Ga, 88 Sr, 89 Y, 91 Zr, 93 Nb, 181 Ta, 208 Pb, and ablating a material with a spot size of 55 μm at a repetition rate of 4 Hz and an energy density of about 21.17 J/cm 2 . Warm up/background time was 90 s, dwell time was 100 s, and wash out time was 120 s. NIST SRM 610 and NIST SRM 612 glasses (National Institute of Standards and Technology; U.S. Department of Commerce: Gaithersburg, MD) were used as the reference materials and ATHO as an unknown for quality control (QCM).…”
Section: Sapphiresmentioning
confidence: 99%
“…In a Fe versus Ga/Mg diagram [14], all measured corundum samples were plotted to "metamorphic" and "plumasitic" population fields ( Figure 6), clearly away from the "magmatic" blue sapphires that are found within syenite pegmatites of Ilmen Mountains (see again [6,17]). However, these trace-element diagrams should be used with the caution and possibly revised, since it was found that some of the sapphires from magmatic deposits could be plotted in the "metamorphic field" [46,47]. It is probably important to refine these plots using solely data of gem-quality samples and to group them by color (e.g., plot sapphire and rubies separately), taking into account that most of trace elements used for these are corundum chromophores (e.g., Fe, Ti, Mg, Cr, V).…”
Section: Comparison Of Chemical Data With Sapphires From Other Geologmentioning
confidence: 99%
“…% oxides). Adapted with permission from [6]; Primorye, Cenozoic alkali basalts [6]; Primorye, placer [6]; Australia, placer [27][28][29][30]; Madagascar [31][32][33]; Vietnam [34]; Cambodia [27,35,36]; and Rwanda [37]. Naryn-Gol-this study.…”
Section: Discussionmentioning
confidence: 99%